Environmentally Relevant Aspects of Nanomaterials in Products at the End-of-life Phase. (December 2015) - Gazsó, André; Fuchs, Daniela; Greßler, Sabine; Gruber, Iris; Part, Florian; Huber-Humer, Marion
Abstract : This section is meant to give readers an insight into the emerging field of nanotechnologies and risk regulation. It informs and updates readers on the latest European and international developments in nanotechnologies and risk regulation across different sectors (e.g., chemicals, food, cosmetics, pharmaceuticals) and policy areas (e.g., environmental protection, occupational health and consumer product, food and drug safety). The section analyzes how existing regulatory systems deal with new kinds of risks and reviews recent regulatory developments with a focus on how best to combine scientific freedom and technological progress with a responsible development and commercialization of nanotechnologies.